Mini-sternotomy for the treatment of aortic valve lesions - Dias,Altamiro Ribeiro (2001)
OBJECTIVE: To compare inverted-L mini-sternotomy performed above the sternal furcula with conventional sternotomy in patients with aortic valve diseases who undergo surgical treatment. METHODS: We operated upon 30 patients who had aortic valve lesions that had clinical and hemodynamic findings. All patients underwent inverted-L sternotomy, which extended from above the manubrium of the sternum to the 3rd right intercostal space, without opening the pleural cavity. Their ages ranged from 32 to 76 years, and 18 were males and 12 were females. We used negative pressure in a venous ¼-inch cannula, and the patients were maintained in Trendelemburg's position. Twenty-seven patients received bioprostheses with diameters ranging from 23 to 29mm. Three patients underwent only removal of the calcifications of the aortic valve leaflets and aortic commissurotomy. RESULTS: The mean duration of anoxic cardiac arrest was 63.11min. Access was considered good in all patients. One death was due to pulmonary and renal problems not related to the incision. All patients had a better recovery in the intensive care unit, got out of bed sooner, coughed more easily, and performed prophylactic physiotherapeutic maneuvers for respiratory problems more easily and with less pain in the incision. Early ambulation was more easily carried out by all patients. CONCLUSION: Mini-sternotomy proved to be better than the conventional sternotomy because it provided morecomfort for the patients in the early postoperative period, with less pain and greater desire for early ambulation and all its inherent advantages.